1989
DOI: 10.1164/ajrccm/140.3_pt_2.s85
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposures: Evidence for a Causal Association with Chronic Obstructive Pulmonary Disease

Abstract: The increase in morbidity and mortality attributable to chronic obstructive pulmonary disease (COPD) has focused attention on environmental and host factors causally associated with the clinical entities included under the rubric of this term with a view to early preventive intervention. Despite the biologic plausibility of inhaled agents being causally implicated, only the role of tobacco smoke has been accepted beyond doubt. However, evidence implicating occupational exposures has accumulated, in particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
143
1
17

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(168 citation statements)
references
References 8 publications
7
143
1
17
Order By: Relevance
“…Certain known risk factors for the exacerbation of COPD were found: no influenza vaccination [7] and high air pollution exposure [8]. In addition, other factors were found, related to the poor progress of the disease, that could be considered potential risk factors for exacerbation: no respiratory rehabilitation [9], underprescription of LTOT and noncompliance with it [10,11], current [12] and passive [13] smoking and occupational exposure [14]. Other potentially relevant factors as suggested by members of the study group were: poor inhaler manoeuvres, no pneumococcal vaccination, consumption of alcohol and sedatives, and no physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…Certain known risk factors for the exacerbation of COPD were found: no influenza vaccination [7] and high air pollution exposure [8]. In addition, other factors were found, related to the poor progress of the disease, that could be considered potential risk factors for exacerbation: no respiratory rehabilitation [9], underprescription of LTOT and noncompliance with it [10,11], current [12] and passive [13] smoking and occupational exposure [14]. Other potentially relevant factors as suggested by members of the study group were: poor inhaler manoeuvres, no pneumococcal vaccination, consumption of alcohol and sedatives, and no physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…As early as 1985, however, Margaret Becklake concluded that occupational exposure to dust and/or dust and fumes may have a causal link to the pathogenesis of COPD, often relying on studies in which work-related factors were included as confounders to be adjusted for in an analysis of smoking effects (9,10). Coggon and Newman Taylor (11) made an extensive analysis of the literature on airflow obstruction among coal miners, concluding there was a significant association between exposure to coal dust and the development of chronic airflow obstruction.…”
mentioning
confidence: 99%
“…Although cigarette smoking is the most important risk factor worldwide for COPD, occupational exposures to mineral and organic dusts, irritant gases and fumes, and to other industrially produced or used agents have been established as risk factors for COPD [2][3][4][5][6][7][8][9][10][11][12][13][14]. Industryand population-based epidemiological studies have reported increased risk of COPD due to occupational exposures or due to employment in certain industries or job categories.…”
Section: Introductionmentioning
confidence: 99%
“…Industryand population-based epidemiological studies have reported increased risk of COPD due to occupational exposures or due to employment in certain industries or job categories. Occupational groups reported to have increased risk of COPD include coal miners, hard rock miners, tunnel workers, concretemanufacturing workers, construction workers, agricultural workers, and some manufacturing workers [2,3,[6][7][8][9]. COPD etiology is multi-factorial in nature and is strongly associated with non-occupational factors such as tobacco smoking.…”
Section: Introductionmentioning
confidence: 99%